Book reviews: Animal spirits. How human psychology drives the economy and why it matters for global capitalism - MANOLESCU, Gheorghe (Annals of Spiru Haret University. Economic Series, 2010)
Animal spirits*. How human psychology drives the economy and why it matters for global capitalism helps us understand how the economic systems operate on the economic theory crisis background. The message of the book is recognizing the importance of irrationality factors in formulating the economic theory. The paper calls for reconsidering the economy fundamentals and principles, presenting a new way of understanding the significant economic phenomena that standard economic science cannot explain or accurately interpret. In this respect, a new way to revolutionize the economic thinking which might change the approach of the economic crises, unemployment, poverty, economic fluctuations and the like, is open. * The “animal spirits” collocation (coming from Latin spiritus animalis, where animus pertains to the soul or means to animate) refers to that nervous fluid presently covering the psychological and emotional motivation factors. In a broad sense, the animal spirits refer to vivacity, to the natural state of a healthy animal, acting as an intermediary between the body and soul. In an economic context, Keynes speaks about the people’s strength and vitality determining them to make bold decisions and to invest money, effort and time in business initiatives. From an economic perspective, the animal spirits cover an element of anxiety and inconsistency present in the economy, the people’s unusual ambiguity and insecurity which sometimes paralyse them, while otherwise stimulate them overcome fear and hesitation.